PERSEPSI SISWA TERHADAP METODE DISKUSI DALAM PEMBELAJARAN BAHASA JEPANG DI SMK TIGAMA PEKANBARU - Fadhilah, Rizkiyatul; Hermandra, Hermandra; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to analyze students' perceptions of the discussion method in learning Japanese at SMK Tigama Pekanbaru. The method used is quantitative description. This research took place at SMK Tigama Pekanbaru. The number of research respondents in this study were students of class X hospitality, which amounted to 12 people and class XII, which amounted to 31 people, which means the total number of samples was 43 students. The data collection technique used a questionnaire technique. The data analysis technique is a descriptive analysis technique or with a percentage. The results of the analysis obtained 4 (four) answer indicators. First, it was analyzed from the interest indicator with an average perception score = 16.64 into the very positive category as many as 12 respondents (32%). Second, analyzed from the attention indicator with an average perception score = 13.48 into the positive category as many as 12 respondents (32%). Third, analyzed from the object indicator with an average perception score = 16.67 into the very positive category as many as 13 respondents (35%). Fourth, analyzed from environmental indicators with an average perception score = 15.32, 15 respondents (41%).Key Words: Perception , Discussion Method, Japanese Language Learning,SMK Tigama Pekanbaru